Methodology of System Management and Expert Assessment - Bogutskyi, Yurii; Kozliuk, Oleksandr; Ridei, Nataliia (Journal of Education, Technology and Computer Science, 2019)
The article deals with the axiological analysis of the terminology apparatus of the general interpretation of the system and its properties; classification features of types of systems; systematic methodology of general, specific, and, in fact, scientific principles and methodological approaches, methodology of system management.